Biomagnetic flow over a flat plate embedded by a magnetic dipole in a porous media - Ferdows, Mohammad; Jumana, Sadia Anjum (Zielona Góra: Uniwersytet Zielonogórski)
The present study used a simplified axisymmetric biomagnetic fluid dynamics and porous media model which includes FHD (Ferrohydrodynamics), porosity and inertia effects saturated by magnetic dipole to study the influences of the leading parameters on various flow variables along a flat plate. The governing equations are simplified and solved by finite difference approach. We clarify how the ferromagnetic interaction parameter, B and porosity,? assumptions contribute in the bio-background of the problem of interest. Moreover, from the results of the flow profiles, accelerating and decelerating phenomena are noticed for B, and ? interaction.
Keywords: porous medium; boundary layer; biomagnetic fluid; dipole